1995
DOI: 10.1093/tropej/41.2.74
|View full text |Cite
|
Sign up to set email alerts
|

The Echocardiographic Findings in Kwashiorkor

Abstract: Echocardiography (ECHO), electrocardiography (ECG), and chest radiography (CXR) were performed in 44 children with kwashiorkor, and 44 age- and sex-matched controls. In patients with kwashiorkor, mean values obtained for end diastolic dimension (29.2 +/- 3.8 mm), end systolic dimension (20.9 +/- 2.8 mm), posterior ventricular wall thickness (5.42 +/- 0.57 mm), and shortening fraction (28.2 +/- 4.3%) were significantly smaller than the corresponding values obtained in the controls -38.0 +/- 5.8 mm (P < 0.001), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…For example, Öcal and colleagues reported a decrease in cardiac output and left ventricular muscle mass proportional to body size in patients with protein-energy malnutrition, but left ventricular systolic and diastolic functions were preserved even in atrophic hearts [46]. Echocardiographic studies examining cardiac function of children affected by severe malnutrition provide conflicting results and have often only investigated children with kwashiorkor [44,47,48]. Most functional studies involve small numbers of patients, with poorly documented contemporaneous data on clinical and hemodynamic status.…”
Section: Effects Of Malnutrition On the Heartmentioning
confidence: 99%
“…For example, Öcal and colleagues reported a decrease in cardiac output and left ventricular muscle mass proportional to body size in patients with protein-energy malnutrition, but left ventricular systolic and diastolic functions were preserved even in atrophic hearts [46]. Echocardiographic studies examining cardiac function of children affected by severe malnutrition provide conflicting results and have often only investigated children with kwashiorkor [44,47,48]. Most functional studies involve small numbers of patients, with poorly documented contemporaneous data on clinical and hemodynamic status.…”
Section: Effects Of Malnutrition On the Heartmentioning
confidence: 99%
“…These may variably influence the cardiac function [4] and may result in an inherent ventricular dysfunction [3]. Myocardial disorders, whether cardiac arrhythmia or heart failure, are responsible for some deaths among kwashiorkor patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Phornphatkul et al (1994) reported that children with malnutrition not only have cardiac muscle wasting but also have inherent ventricular dysfunction as a result of severe malnutrition that responds to nutritional therapy. It has been reported that myocardial dysfunction either in the form of cardiac arrhythmia or heart failure are among the causes of death in kwashiorkor (Olowonyo et al, 1995).…”
Section: Introductionmentioning
confidence: 99%